Desenvolvimento e caracterização de oleogéis elaborados com diferentes óleos vegetais e agentes estruturantes visando aplicação em alimentos. - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2022)
The growing demand to reduce and eliminate saturated and trans fats due to their relationship with cardiovascular diseases, and other disorders in the body, has generated the development of other alternatives to the fats traditionally used in food processing. But, the great challenge is to give technological functionality to lipids rich in unsaturated fatty acids, but with a viable and promising approach. Oleogels are systems composed of a lipid base constituted by oil structured by a three- dimensional network of structuring agents. Therefore, the objective of this work was to investigate the influence of different vegetable oils and structuring agents in the oleogels formed, defined by their physicochemical characteristics, on their physical, thermal, structural and rheological properties Oleogels structured with MG and canola and linseed oil take 45 and 25 minutes to gel, respectively, and oleogels with EA take 6 to 7 minutes, but their oil retention capacity is the lowest (89%), which may be related to its needle-shaped microstructure that differs it from all other structurants. The color was directly affected due to the color of the oil used, formulations with linseed oil had the greatest tendency to yellow. The structuring mixtures with canola oil increased the stability temperature, and the highest oxidation onset temperatures were those that had CC as a structuring agent, reached about 211oC. Samples with CC and MG are more stable, presenting a flow point at a temperature close to 80oC and 65oC. Finally, this work contributed to the expansion of knowledge of the systems called oleogels, suggesting that future works guide the choices of raw materials for the formulation of oleogels on the properties of their components.
Keywords: Planejamento de Misturas; Reologia; Estabilidade; Cristalização; Mixture Design; Rheology; Stability; Crystallization; CNPQ::CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS